SOFT PNEUMATIC ACTUATOR DESIGN FOR HAND REHABILITATION ROBOT USING MODELING BASED ON FINITE ELEMENT METHOD - Fidinillah, Tsabita
In the conduct of daily life activities, the movement of fingers and hands is deemed essential. The ramifications of the loss of these motor capabilities are substantial, resulting in a discernible decline in an individual's overall quality of life. Although physical therapy has demonstrated efficacy in restoring hand function through repetitive tasks, its success is contingent upon consistent and extended engagement under the guidance of a skilled therapist. To address the significance of repetitive flexion-extension exercises, the integration of rehabilitation robotics has emerged as a necessity, facilitating the development of a system conducive to independent patient exercises. Traditional rigid robotic rehabilitation modalities, grounded in an electro-mechanical paradigm utilizing DC/stepper motors as actuators, face challenges in achieving designs characterized by personalization and ergonomic accommodation tailored to individual patient needs and distinct physiological conditions.